Growing Up With Parents Who Have Learning Difficulties. - Booth, Timothy A. (Routledge, 1998)
Provides new evidence and insights derived from original research and life stories to answer questions about what it means for a child to be brought up by a parent with learning difficulties and whether this affects their well-being.